2021
DOI: 10.1002/jlb.1a0920-588r
|View full text |Cite
|
Sign up to set email alerts
|

Loss of mTORC2-induced metabolic reprogramming in monocytes uncouples migration and maturation from production of proinflammatory mediators

Abstract: Monocyte migration to the sites of inflammation and maturation into macrophages are key steps for their immune effector function. Here, we show that mechanistic target of rapamycin complex 2 (mTORC2)‐dependent Akt activation is instrumental for metabolic reprogramming at the early stages of macrophage‐mediated immunity. Despite an increased production of proinflammatory mediators, monocytes lacking expression of the mTORC2 component Rictor fail to efficiently migrate to inflammatory sites and fully mature into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…We observed that lack of signaling through mTORC2 in CD11c+ cells inhibits actin cytoskeleton organization and migration. Supporting our findings, our group (53) and a recent study by Jangani (54) demonstrated that loss of mTORC2 activity impairs the migration of neutrophils and monocytes, respectively. Cytoskeleton organization and motility in humans and murine DCs have been classically associated with the Rho family GTPases (33,40,41).…”
Section: Discussionsupporting
confidence: 88%
“…We observed that lack of signaling through mTORC2 in CD11c+ cells inhibits actin cytoskeleton organization and migration. Supporting our findings, our group (53) and a recent study by Jangani (54) demonstrated that loss of mTORC2 activity impairs the migration of neutrophils and monocytes, respectively. Cytoskeleton organization and motility in humans and murine DCs have been classically associated with the Rho family GTPases (33,40,41).…”
Section: Discussionsupporting
confidence: 88%
“…In line with the ability of NOD2 signalling to activate Signal transducer and activator of transcription 5 (STAT5) 47 , the treatment of THP1 cells with MDP significantly lowered the expression of IRF8 that is inhibited by STAT5 (SFig8C). Altogether, these results indicate that NOD2 signalling of monocytes may interfere with the PI3K/mTORC1 pathway through the mTORC2/AKT complex, which may inhibit diversion of monocyte differentiation to macrophages via metabolic reprogramming 43 . In other words, these data suggest that MDP induces a transient negative regulation of mTOR pathway to limit accumulation of inflammatory macrophages, leading to an unrepressed generation of mo-DCs.…”
Section: Nod2 Activates Mtorc2 Pathway and Promotes Anaerobic Glycolysismentioning
confidence: 84%
“…At this time point, immunoblot analysis expectedly revealed that treatment with MDP did not induce the phosphorylation of S6K, which is a surrogate marker of mTORC1 activation (SFig8B). As mTORC2 pathway plays a key role in the glycolytic reprogramming of monocytes that are rapidly mobilized on demand 43,44 , we next investigated if MDP treatment of monocytes is associated with changes in mTORC2-mediated metabolic cascade. To this end, previously published RNAseq data for MDP-treated Ly6C hi mouse monocytes (GEO accession number GSE101496) were mined for candidate genes encoding for enzymes involved in glycolysis.…”
Section: Nod2 Activates Mtorc2 Pathway and Promotes Anaerobic Glycolysismentioning
confidence: 99%
“…We demonstrate that miRNA-326-3p drives mitochondrial dysfunction in NMVMs through inhibiting the translation of Rictor. Although mTORC2 is associated with cell metabolism [ 55 , 56 ] yet its role in cardiomyocytes remains to be explored. Given that Rictor is at the heart of the mTORC2 complex, we speculate based on previous work that loss of Rictor in STZ murine cardiomyocytes likely results in attenuation of metabolite influx into mitochondria [ 57 ], blocked connexin 43 localization to mitochondria [ 58 ], and mitochondrial dysfunction [ 59 ].…”
Section: Discussionmentioning
confidence: 99%